Role of Media in Tentara Kandjeng Nabi Muhammad and Aksi Bela Islam 212 - Kurniawan, Vicky; Asnan, Gusti; Djalius, Yusmarni (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The Tentara Kandjeng Nabi Muhammad (TKNM) movement emerged following the publication of an article insulting the Prophet Muhammad by the Djawi Hisworo newspaper on 1918, while the Aksi Bela Islam 212 movement arose in response to blasphemy allegations against Basuki Tjahaja Purnama (Ahok) in 2016. TKNM was the largest movement during the colonial period, and Aksi Bela Islam 212 became the largest post-colonial movement in Indonesia, both heavily influenced by media. This study examines the role of media in the TKNM and Aksi Bela Islam 212 movements using a comparative historical approach, involving heuristic, verification, interpretation, and historiography stages. Findings reveal a power-media relationship in the rise of mass movements, alongside political factors contributing to the mobilization of TKNM and Aksi Bela Islam 212, led respectively by prominent figures Tjokroaminoto and Habib Rizieq.